Electrophoretic patterns of human rotavirus strains prevailing among hospitalized children with acute gastroenteritis (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):49-54The abstract of this article is available on the PubMed website